2021
DOI: 10.1001/jamanetworkopen.2021.30674
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diversion Strategies for Management of Acute Complicated Diverticulitis in a US Nationwide Cohort

Abstract: IMPORTANCE Diverticulitis of the colon is an increasingly prevalent disease with significant implications for patient quality of life and health system resource expenditure. Although several randomized clinical trials and meta-analyses of Hartman procedure (HP) and primary anastomosis and proximal diversion (PAPD) have found surgical equipoise, questions regarding the relative performance of these treatments when applied broadly remain. OBJECTIVE To examine use of and outcomes after urgent sigmoid colectomy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…A meta-analysis of the aforementioned RCTs 2 suggested this conclusion. However, while Sanaiha and colleagues 7 found similar index outcomes between PAPD and HP, they did not find advantages of PAPD compared with HP during index admission.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…A meta-analysis of the aforementioned RCTs 2 suggested this conclusion. However, while Sanaiha and colleagues 7 found similar index outcomes between PAPD and HP, they did not find advantages of PAPD compared with HP during index admission.…”
mentioning
confidence: 84%
“…Prior analysis of the New York State All Payer Database by Goldstone et al 6 found that colorectal board certification was associated with increased use of PAPD and decreased postoperative mortality. While the NRD lacks surgeon-specific data, sensitivity analysis in the study by Sanaiha et al 7 found decreased mortality and complication rates when PAPD was performed at hospitals with increased volume of emergency general surgical procedures (>50 procedures per year). Finally, while several index outcomes were similar with PAPD and HP in adjusted analyses, there is a significant selection bias associated with which patients are offered PAPD outside of an RCT setting.…”
Section: + Related Articlementioning
confidence: 99%
See 1 more Smart Citation
“…7 Surgeon preference is the main factor in choosing an ostomy for perforated diverticulitis. 7 Diversion not only allows the healing of a higher risk anastomosis but also increases the likelihood of restoring bowel continuity. Stoma reversal rates are observed to be much lower in Hartmann's patients (30-57%) compared with a diverting ileostomy (90-95%).…”
mentioning
confidence: 99%
“…In the acute setting, the performance of a primary anastomosis with diversion is becoming more popular. 7 Surgeon preference is the main factor in choosing an ostomy for perforated diverticulitis. 7 Diversion not only allows the healing of a higher risk anastomosis but also increases the likelihood of restoring bowel continuity.…”
mentioning
confidence: 99%